PENINGKATAN HASIL BELAJAR IPS PADA SISWA KELAS V SEKOLAH DASAR INPRES SAMOFA DISTRIK BIAK KOTA - Nap, Maryana; Laka, Beatus Mendelson; Meokbun, Naftali (Metodik Didaktik : Jurnal Pendidikan Ke-SD-an, 2020)
The purpose of the study was to determine the process of improving learning outcomes and the difficulties encountered by the teacher in an effort to improve social studies learning outcomes of students of SD Inpres Samofa. The research method used was descriptive qualitative research. The results showed that the process of improving learning outcomes carried out by the teacher has carried out aspects of learning which include (1) pre-learning which is to determine the readiness of students in following learning activities, (2) activities to open learning including beginning with prayer, giving greetings and giving direction, (3) these activities include checking the readiness of students, delivering subject matter, (4) closing including evaluating the material that students have learned well. For teachers in SD Inpres Samofa there are no difficulties in finding teachers in an effort to improve students' social studies learning outcomes in SD Inpres Samofa because the teachers who teach at SD Inpres Samofa have served long enough so that students are already comfortable with the teachers at the school.